The impact of artificial intelligence techniques on marketing innovation: an applied study on Mobily company in Saudi Arabia - Alotaibi, Maha Mohammed; Al-Youbi, Layla Abed (Journal of Humanities & Social Sciences, 2024)
This study aims to determine the impact of (AI) technologies on marketing innovation at Mobily Company. by highlighting the most prominent AI technologies that significantly affect organizational performance, and marketing innovation which is considered a source of advantage for companies and countering competitors , The study adopted a case study approach to examine the current situation at Mobily Company and assess the extent of AI technology application in marketing innovation , To confirm the hypotheses that state that there is a statistically effect of 0.05 , and a statistically relationship for artificial intelligence technologies on marketing innovation in Mobily, The study relied on a scientific questionnaire and was conducted within the company’s three main branches in the city of Mecca, and using the content analysis approach to prepare a proposed model to clarifying how artificial intelligence techniques are used in marketing innovation. The study found the utilization of (AI) at Mobily Company has a favorable effect on marketing innovation (80%). and there is a strong statistically significant correlation for artificial intelligence techniques and marketing innovation in Mobily (93%), the big data analytics technology had the highest impact on marketing innovation by (59%), While deep learning technology least impact on marketing innovation (27%), the study recommended adoption (AI) technologies in marketing innovation in its dimensions to facilitate the handling of big data and create products that meet the customer’s desires, And prepare a development plan for big data analysis technology as it is most influential artificial intelligence technology on marketing innovation.